2010
DOI: 10.1371/journal.pone.0010915
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bacterial Killing In Vitro by Recombinant Nod2 Is Compromised by Crohn's Disease-Associated Mutations

Abstract: BackgroundA homeostatic relationship with the intestinal microflora is increasingly appreciated as essential for human health and wellbeing. Mutations in the leucine-rich repeat (LRR) domain of Nod2, a bacterial recognition protein, are associated with development of the inflammatory bowel disorder, Crohn's disease. We investigated the molecular mechanisms underlying disruption of intestinal symbiosis in patients carrying Nod2 mutations.Methodology/Principal FindingsIn this study, using purified recombinant LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Prior studies demonstrated that NOD2 is an essential mediator of host defense against a variety of intracellular pathogens such as Listeria monocytogenes (56), Mycobacterium tuberculosis (23,54), and Legionella pneumophila (9). In addition, it has been demonstrated that murine macrophages require NOD2 to respond to Staphylococcus aureus infection (31).…”
mentioning
confidence: 99%
“…Prior studies demonstrated that NOD2 is an essential mediator of host defense against a variety of intracellular pathogens such as Listeria monocytogenes (56), Mycobacterium tuberculosis (23,54), and Legionella pneumophila (9). In addition, it has been demonstrated that murine macrophages require NOD2 to respond to Staphylococcus aureus infection (31).…”
mentioning
confidence: 99%
“…• Dysbiosis was confirmed in uninvolved HS skin by 3 teams. 6,76,77 • An immune deficiency towards commensal gut flora was reported in patients with Crohn's disease carrying a NOD2 mutation, 78 while some HS patients can present with both diseases.…”
Section: Furthermorementioning
confidence: 99%
“…Their expression is normally associated with myeloid and non-lymphoid cell types. Upon ‘sensing’ these ligands via leucine rich repeat domains (LRR)(3, 4), dimerization occurs via the oligomerization domain, leading to caspase-recruitment domain (CARD) dependent interaction with the serine threonine kinase RIP2 (Receptor interacting protein 2) (57). The peptidoglycan ligand activated NOD: RIP2 complex promotes the potent activation of NFκB, leading to the production of inflammatory mediators and chemokines (8).…”
Section: Introductionmentioning
confidence: 99%